5(6+8B)+8(B-5)=-10

Simple and best practice solution for 5(6+8B)+8(B-5)=-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(6+8B)+8(B-5)=-10 equation:


Simplifying
5(6 + 8B) + 8(B + -5) = -10
(6 * 5 + 8B * 5) + 8(B + -5) = -10
(30 + 40B) + 8(B + -5) = -10

Reorder the terms:
30 + 40B + 8(-5 + B) = -10
30 + 40B + (-5 * 8 + B * 8) = -10
30 + 40B + (-40 + 8B) = -10

Reorder the terms:
30 + -40 + 40B + 8B = -10

Combine like terms: 30 + -40 = -10
-10 + 40B + 8B = -10

Combine like terms: 40B + 8B = 48B
-10 + 48B = -10

Add '10' to each side of the equation.
-10 + 10 + 48B = -10 + 10

Combine like terms: -10 + 10 = 0
0 + 48B = -10 + 10
48B = -10 + 10

Combine like terms: -10 + 10 = 0
48B = 0

Solving
48B = 0

Solving for variable 'B'.

Move all terms containing B to the left, all other terms to the right.

Divide each side by '48'.
B = 0

Simplifying
B = 0

See similar equations:

| m-4m+12=3 | | 5x+10=9x+15 | | [(x-2)-5][(x-2)+3]=0 | | 18+2x=-54 | | 17x+64=13 | | -256=8(7X-6)-4X | | 24x+7*8= | | 5a-2+b-3b+2a= | | 5x-3x+40=50 | | x+109=1+89 | | 3x^2-8x-19=0 | | 70=-17.5n | | 2x=3x-10 | | 12v-3(2+4v)+6= | | 6(1-6X)-4(3X+6)=30 | | -15x+7x+1=3-8 | | 3x^2-22x=0 | | 3x^2-32x-19=0 | | 20x^3-8x^2-5x+2=0 | | 100-x=-39 | | 40-x=-5 | | -4(y-3)+6=2(2y-2)+5y+5 | | 6n^3-24n^2+n-4=0 | | 5+n-p+2n-4= | | 4x-3y=42 | | 4x+3y=42 | | [2x+4]=8 | | 1+1+1=A | | 2(2t+5-2t)+8t= | | 6456*6557-7567+6678/66788+(676+9*5)=s | | m^2+2m-12=0 | | -(y-11)=-3 |

Equations solver categories